Effect of Voxel Size of Micro-CT on the Assessment of Root Canal Preparation - Pinto, Jader Camilo; Lucas-Oliveira, Everton; Bonagamba, Tito Jose; Guerreiro-Tanomaru, Juliane Maria; Tanomaru-Filho, Mario (Odovtos - International Journal of Dental Sciences, 2023)
The aim of this study was to assess the influence of micro-computed tomography (micro-CT) voxel size on evaluation of root canal preparation using rotary heat-treated nickel-titanium files. Curved mesial root canals of mandibular molars were prepared using ProDesign Logic 30/.05 (PDL) or HyFlex EDM 25/.08 (HEDM) (n=12). The specimens were scanned using micro-CT with 5μm of voxel size before and after root canal preparation. Images with sub-resolution of 10 and 20μm voxel sizes were obtained. The percentage of volume increase, debris and uninstrumented root canal surface were analyzed in the different voxel sizes. Data were compared using unpaired Student’s t-test and ANOVA statistical tests (α=0.05). No differences were observed for percentage of volume increase, debris and instrumented surface between the root canals prepared by PDL and HEDM (p>0.05). Both systems promoted higher percentage of debris in the apical third compared to the middle third (p<0.05). After instrumentation using PDL the percentage of uninstrumented surface was highr in the apical third than middle third only when analysis were performed at 5µm (p<0.05). When comparing the different voxel sizes (5,10 or 20µm), both groups showed different means for the variables, with no significant difference (p>0.05). PDL and HEDM had similar root canal preparation capacity. Micro-CT images using different voxel sizes did not influence the results of volume increase and debris evaluation. However, images at 5µm showed greater accuracy to evaluate the percentage of uninstrumented surfaces.